Penggunaan dan penilaian kualiti laman web agensi-agensi pertanian oleh para pegawai pertanian di Malaysia - Ahmad Fahmi, Mahamood; Noraida, Nordin; Hanif Suhairi, Abu Bakar (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.